SUN-557 Thymic Hyperplasia in Graves' Disease: A Case Series - Voss, Michael (J Endocr Soc, 2019)
Background: Thymic hyperplasia (TH) is a known, but often under-recognized finding associated with Graves' disease (GD). The exact pathophysiology of GD-related TH is poorly understood, but is thought to be benign. Limited case reports or series indicate resolution or improvement of TH following successful treatment of GD. Although TH is often incidentally found, discovery can be alarming resulting in potentially inappropriate intervention. Therefore, increased awareness regarding GD-related TH is necessary to avoid this. Aim: To describe the natural history of GD-related TH and assess for risk factors which may be associated with the development of TH. Methods: Retrospective review of patients referred to a tertiary referral center with GD with an anterior mediastinal mass on computed tomography (CT) scan suspected to be TH. Clinical Cases: In total, six patients (30-51 years of age) were discovered to have an anterior mediastinal mass on CT scan at time of GD diagnosis. The majority were women (5/6). Although three patients had a family history of thyroid autoimmunity, only one patient had a co-existing autoimmune condition (Vitiligo). Two patients were active smokers. All patients presented to the emergency room with significant thyrotoxic symptoms including tachycardia (107-170 beats per minute) and weight loss (18.3 ± 11.8 kg) with four requiring admission. One patient presented with thyroid storm. Laboratory testing revealed high circulating thyroid hormone levels at diagnosis with mean free T4 level of 4.24 ± 1.56 ng/dL (0.6-1.76) as well as high mean thyroid-stimulating immunoglobulin activity level of 306.2% (≤122). Clinically significant Graves'-associated orbitopathy was observed in 67% of patients. Tachycardia was the cited reason for requested CT imaging in all patients. The size of thymus glands varied with the largest measuring 9cm x 1cm x 5cm. All thymic masses were consistently characterized as homogeneous without discrete lesions or calcifications. Though only two patients received follow-up chest imaging, both patients demonstrated > 50% reduction in thymus size at six months and no patients underwent biopsy or surgical excision. All but one of our patients required definitive therapy for poorly controlled hyperthyroidism on thionamides (Three had surgery of whom two had severe Graves' orbitopathy and two underwent radioactive iodine therapy). Conclusions: While the true incidence of GD-associated TH is unknown, increased use of imaging modalities may result in further incidental discoveries. Therefore, clinicians need to be aware of the association between benign TH and GD to avoid unnecessary invasive interventions. Furthermore, our findings suggest that GD-related TH may be a marker of GD severity with a lower likelihood of GD remission using thionamides necessitating definitive therapy.